HO-1 Upregulation by Kaempferol via ROS-Dependent Nrf2-ARE Cascade Attenuates Lipopolysaccharide-Mediated Intercellular Cell Adhesion Molecule-1 Expression in Human Pulmonary Alveolar Epithelial Cells - Chien-Chung Yang; Li-Der Hsiao; Chen-Yu Wang; Wei-Ning Lin; Ya-Fang Shih; Yi-Wen Chen; Rou-Ling Cho; Hui-Ching Tseng; Chuen-Mao Yang (MDPI AG, 2022)
Lung inflammation is a pivotal event in the pathogenesis of acute lung injury. Heme oxygenase-1 (HO-1) is a key antioxidant enzyme that could be induced by kaempferol (KPR) and exerts anti-inflammatory effects. However, the molecular mechanisms of KPR-mediated HO-1 expression and its effects on inflammatory responses remain unknown in human pulmonary alveolar epithelial cells (HPAEpiCs). This study aimed to verify the relationship between HO-1 expression and KPR treatment in both in vitro and in vivo models. HO-1 expression was determined by real time-PCR, Western blotting, and promoter reporter analyses. The signaling components were investigated by using pharmacological inhibitors or specific siRNAs. Chromatin immunoprecipitation (ChIP) assay was performed to investigate the interaction between nuclear factor erythroid-2-related factor (Nrf2) and antioxidant response elements (ARE) binding site of HO-1 promoter. The effect of KPR on monocytes (THP-1) binding to HPAEpiCs challenged with lipopolysaccharides (LPS) was determined by adhesion assay. We found that KPR-induced HO-1 level attenuated the LPS-induced intercellular cell adhesion protein 1 (ICAM-1) expression in HPAEpiCs. KPR-induced HO-1 mRNA and protein expression also attenuated ICAM-1 expression in mice. Tin protoporphyrin (SnPP)IX reversed the inhibitory effects of KPR in HPAEpiCs. In addition, in HPAEpiCs, KPR-induced HO-1 expression was abolished by both pretreating with the inhibitor of NADPH oxidase (NOX, apocynin (APO)), reactive oxygen species (ROS) (N-acetyl-L-cysteine (NAC)), Src (Src kinase inhibitor II (Srci II)), Pyk2 (PF431396), protein kinase C (PKC)α (Gö6976), p38 mitogen-activated protein kinase (MAPK) inhibitor (p38i) VIII, or c-Jun N-terminal kinases (JNK)1/2 (SP600125) and transfection with their respective siRNAs. The transcription of the homx1 gene was enhanced by Nrf2 activated by JNK1/2 and p38α MAPK. The binding activity between Nrf2 and HO-1 promoter was attenuated by APO, NAC, Srci II, PF431396, or Gö6983. KPR-mediated NOX/ROS/c-Src/Pyk2/PKCα/p38α MAPK and JNK1/2 activate Nrf2 to bind with ARE on the HO-1 promoter and induce HO-1 expression, which further suppresses the LPS-mediated inflammation in HPAEpiCs. Thus, KPR exerts a potential strategy to protect against pulmonary inflammation via upregulation of the HO-1.